Games for Grammar Practice: A resource book of grammar games and interactive activities - Zaorob M. L. Maria Lucia (Cambridge Copy Collection)
Games for Grammar Practice is a teacher's resource book containing a selection of more than forty games and activities for grammar practice. The activities are designed omote intensive and interactive practice with learners all ages from elementary to advanced level. Photocopiable pages and step-by-step instructions provide instant supplementary activities for busy teachers. The emphasis on peer interaction and co-operation helps students find grammar practice meaningful and The grammar areas covered in the book are all commonly found in courses, making the activities e to slot into a lesson.